The problem of student migration in the Republic of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
The social and demographic situation is significantly influenced by migration processes, i.e. the decline and influx of population. If the number declining population will significantly prevail over the number of arrivals of the population can cause problems such as a decline in the birth rate and reduce the number of young population, i.e. will the aging population and the decline of the species and will experience a loss of future specialists with high intellectual and creative abilities (loss of economically active population). Also, most information resources highlight such negative consequences of student migration processes as the growth of illegal migration (migrants have a low standard of living and social conditions); the growth of social tension (between immigrants and society) due to national, cultural, religious and other differences in the new country; problems with employment in the new place. Young people, students and graduates are an intellectual potential and an important component in the development of society, a special group with a good level of mobility, intellectual activity and health, which give them an advantage over other categories of the population, represent the economic and demographic potential of the country, so the migration losses of students are undesirable in the country. Higher education in Kazakhstan has improved significantly in recent years. The government of Kazakhstan is making every effort to improve the higher education system, focusing on research, innovation and science. The Ministry of education has a special program at the invitation of foreign professors in Kazakhstan universities. When the quality of higher education in Kazakhstan becomes more competitive in the world, why do Kazakh students still want to study abroad? The article is written in the framework of the scientific project of the Ministry of education and science of the Republic of Kazakhstan “Educational migration from Kazakhstan: factors, trends and social and political consequences”.Key words: educational migration, higher education, universities, youth, state, UNESCO.